Hyaluronic acid and its use in non-hormonal therapy for the treatment of vaginal atrophy and the level of awareness about the disease itself among the women from the Podkarpackie Voivodeship - Agata Glac; Kinga Musz; Katarzyna Dobko; Gabriela Frącz; Klaudia Kuliga; Natalia Sejnowska; Agnieszka Socha; Agata Surowiec; Kinga Śnieżek; Anna Zając (Quality in Sport, 2023)
Introduction: Hyaluronic acid is the ingredient contained in the composition that has the ability to bind water, found in the cornea, synovial fluid and cartilage stroma. Its properties are suitable for use in an increasing range of fields, both aesthetic and in treatments focusing on the treatment of vaginal atrophy.